- #1
iceman_ch
- 33
- 0
Ok, I have two question that have me stuck. I understand heavyside functions and how to do a laplace transform on them but, they've thrown me a curve ball. I'm sure I'm just making it more complicated then it needs to be.
Here is problem number one.
g(t) = 2t for 0 <= t < 1;
2 for 1 <= t;
This is the same as:
g(t) = 2tH(t) - 2tH(t-1) + 2H(t-1)
The next step is were I'm confused. The book finished setting up this problem for a laplace transform by changing the equation to this:
g(t) = 2tH(t) - 2(t-1)H(t-1)
Why did they change it like this and how did they do this. I'm know I'm over looking something but, I'm not sure what. Any help would be great.
Here is problem number one.
g(t) = 2t for 0 <= t < 1;
2 for 1 <= t;
This is the same as:
g(t) = 2tH(t) - 2tH(t-1) + 2H(t-1)
The next step is were I'm confused. The book finished setting up this problem for a laplace transform by changing the equation to this:
g(t) = 2tH(t) - 2(t-1)H(t-1)
Why did they change it like this and how did they do this. I'm know I'm over looking something but, I'm not sure what. Any help would be great.